PENGARUH IKLIM ORGANISASI, WORK LIFE BALANCE DAN ETOS KERJA TERHADAP KINERJA PEGAWAI NEGERI SIPIL PADA DINAS PEKERJAAN UMUM DAN PENATAAN RUANG KOTA - Wulandari, Ni Wayan Regita; Pratama, Octavianus Sumardana (Jurnal MBE Manajemen Bisnis, Equilibrium, 2024)
The purpose of this study was to determine the effect of organizational climate, work life balance and work ethic on the performance of civil servants at the Department of Public Works and Spatial Planning in Denpasar City. This study used observation, interview, questionnaire and documentation methods with a sampling technique, namely the proportional random sampling technique with a total sample of 56 employees. Data were analyzed using instrument test, classical assumption test, multiple linear regression analysis, coefficient of determination, t test and f test. The results of the analysis show that organizational climate, work life balance and work ethic simultaneously have a positive and significant effect on employee performance. Organizational climate has a positive and significant effect partially on employee performance. Work life balance has a positive and significant effect partially on employee performance. Work ethic has a partial positive and significant effect on employee performance at the Department of Public Works and Spatial Planning in the City of Denpasar.